Making medical devices safer: impact of plastic and silicone oil on microbial biofilm formation. Issue 1 (September 2020) - Slettengren, M.; Mohanty, S.; Kamolvit, W.; van der Linden, J.; Brauner, A.
Summary: Background: Medical devices face the challenge of microbial biofilm attached to the surface. Ultimately, this may jeopardize the function of the device and increase the patient's risk of infection. However, reliable methods to prevent biofilm are lacking. Aim: To investigate the effect of silicone oil-coated polypropylene plastic, used in a new automatic urinometer, on biofilm formation; furthermore, to explore the impact of silicone oil viscosity and compare polypropylene with polystyrene, another common medical plastic. Methods: Common pathogens, including extended-spectrum beta lactamase (ESBL) -producing and multi-drug-resistant bacteria, as well as Candida albicans, were investigated. Isogenic Escherichia coli strains deficient in the important biofilm forming factors curli, cellulose and type 1 fimbriae ( fim D ) were used to determine the possible mode of action by silicone oil. Clear flat-bottomed polypropylene or polystyrene wells were pretreated with either low- or medium-viscosity silicone oil and microbes were added. After 72 h, biofilm formation was quantified using crystal violet assay. Findings: Silicone oil-coated polypropylene plastic surfaces, regardless of the oil viscosity, significantly inhibited biofilm formation of all tested Gram-negative and Gram-positive bacteria, including ESBL-producing and multi-drug resistant strains, as well as C. albicans . Silicone oil did not affect bacterial or candida growth and curli fimbriae were found to be the main target of silicone oil. Polypropylene plastic itself without oil had a better effect in preventing biofilm formation than polystyrene. Conclusion: These findings suggest a new strategy to decrease microbial biofilm formation, which may reduce hospital-acquired infections and prevent dysfunction of medical devices.